Effect of temperature on development and survival of Citrostichus phyllocnistoides (Hymenoptera: Eulophidae), a parasitoid of Phyllocnistis citrella (Lepidoptera: Gracillariidae) - Urbaneja, Alberto; Morales, C.; Hermoso-De-Mendoza, Alfonso; Garrido, Antonio; Jaques, Josep A. (2017)
Thermal requirements of Citrostichus phyllocnistoides under laboratory conditions resulted in a lower temperature threshold of 9.8°C and a thermal constant of 212.0 DD. Development was completed between 15 and 30°C, but was not at 10°C. Therefore, the overwintering of this exotic biocontrol agent would be possible under typical Mediterranean temperatures.